Caracterização fitoquímica das cascas do caule de Terminalia argentea (Combretaceae) e atividades biológicas - Oliveira, Geovane de (2024)
Species of the Terminalia genus are distributed in tropical regions around the globe and are used for medicinal purposes by various cultures in the treatment of diseases, bacterial infections, sore throats, ulcers, conjunctivitis, heart diseases, skin diseases, pneumonia, hookworm, diarrhea, hypertension, nosebleeds, leprosy, and jaundice. The species Terminalia argentea Mart and Zucc naturally occurs in the cerrado, the Atlantic forest, the Amazon forest, and the caatinga, its bark is popularly used in the treatment of canker sores, tumors, and to calm coughs, the infusion of its leaves is used in the treatment of ulcers. This study describes the isolation and structural elucidation of the substances 3-Oglycopyranoside 8-methyl-beta-sitosterol, beta sitosterol glycopyranoside, 3-Omethylellagic acid-4’-α-rhamnopyranoside, arjunentin, in addition to the identification of the presence of quercetin, gallic acid, rutin, and isorhamnetin by investigation using HPLC. Tests were also carried out for antioxidant activity, with the oomycete Phytium insidiosum causing pythiosis. With the exception of the chloroform fraction, all other fractions demonstrated activity in inhibiting the development of the oomycete P. insidiosum, with the best results reserved for the crude ethanolic extract and the hydromethanolic residue of its liquid-liquid partition. Regarding antioxidant activity, at a concentration of 0.3 mg/mL, with the exception of the hydromethanolic residue, all fractions and the crude extract demonstrated significant activity in preventing intracellular oxidation in the BY4741 strain of S. cerevisiae stressed with hydrogen peroxide. The antinociceptive activity was evaluated by the model of induction of abdominal contortions by acetic acid in rodents. From the concentration of 300 mg/kg all tested fractions showed activity, with emphasis on the ethanolic extract of the leaves that showed activity similar to the control group treated with morphine and superior when the concentration was increased to 500 mg/mL. The antidermatogenic activity was tested through the model of paw edema induced by carrageenan, for which the best result observed was in relation to the activity of the crude ethanolic extract of the bark of the T. argentea stem, which showed a decrease in induced edema similar to the control group for a concentration of 500 mg/kg. The study was able to achieve its objectives by demonstrating potential therapeutic potentials of different parts of the plant that can be correlated to their uses by traditional communities, in addition to contributing to the chemical taxonomy of the species through the isolation of compounds.